HUBUNGAN KECERADASAN SPRITUAL DAN MOTIVASI BELAJAR DENGAN PRESTASI BELAJAR MATA PELAJARAN PENDIDIKAN AGAMA ISLAM - Riska Handayani; Adibah; Muhtadi (FAI- Undar, 2017)
Primary School laid the foundation of intelligence, knowledge, personality, character and skills to live independently and to follow further education. And subjects of Islamic education is a very important subject in school. So that students graduate primary school is expected to have the provision of sufficient religious knowledge, so they can practice the religion of science in society.By looking on the events and the facts, the purpose of this research are: 1) To determine the relationship with the Spiritual Intelligence Learning Achievement of Islamic Education in Elementary School Podoroto I Kesamben Jombang. 2) To determine the relationship with Learning Achievement Motivation Islamic Religious Education at Elementary School Podoroto I Kesamben Jombang. 3) To know Relations and Motivation Spiritual Intelligence, with the same with the Islamic Religious Education Learning Achievement in Elementary School Podoroto I Kesamben Jombang.This research method using quantitative research design because the symptoms are the tangible results of research data is measured and converted in advance in the form of numbers or quantified and analyzed using statistical techniques. Population and samples were taken using the technique of